Caught in the net how to recognize the signs of Internet addiction--and a winning strategy for recovery - Young, Kimberly S. (John Wiley & Sons, 1998)
Internet addiction is real. Like alcoholism, drug addiction, or compulsive gambling, it has devastating effects on the lives of addicts and their families: divorce, job loss, falling productivity at work, failure in school, and, in extreme cases, criminal behavior. The problem has already reached epidemic proportions in the United States, and the number of "netaholics" continues to grow rapidly as more households and businesses go on-line. Yet, until now, no one from the mental health community has come forward with a specific description of Internet addiction and its effects or a strategy for treatment and recovery. The author shares the results of her three-year study of Internet abuse. Often using the words of the Internet addicts themselves, she presents the stories of dozens of lives that were shattered by an overwhelming compulsion to surf the Net, play MUD games, or chat with distant and invisible neighbors in the timeless limbo of cyberspace. Why is the Internet so seductive? What are the warning signs of Internet addiction? Is recovery possible? Dr. Young answers these questions and many more. She provides a questionnaire to help Net users determine whether they are addicts, and offers concrete steps to help problem users regulate Internet usage and devise a more balanced place for it in their daily lives. For Internet addicts as well as their parents, spouses, friends, and employers, this book offers guidance on where and how to seek help from counselors, therapists, and other professionals who take this affliction seriously. For mental health professionals, this book provides insights into the nature and causes of Internet addiction and encourages counselors and therapists to expand their addiction recovery programs to address the specific problems of Internet addicts.